Elucidation of the molecular responses to waterlogging in Jatropha roots by transcriptome profiling - Juntawong, Piyada; Sirikhachornkit, Anchalee; Pimjan, Rachaneeporn; Sonthirod, Chutima; Sangsrakru, Duangjai; Yoocha, Thippawan; Tangphatsornruang, Sithichoke; Srinives, Peerasak (Frontiers in Plant Science, 2014)
Jatropha (Jatropha curcas) is a promising oil-seed crop for biodiesel production. However, the species is highly sensitive to waterlogging, which can result in stunted growth and yield loss. To date, the molecular mechanisms underlying the responses to waterlogging in Jatropha remain elusive. Here, the transcriptome adjustment of Jatropha roots to waterlogging was examined by high-throughput RNA-sequencing (RNA-seq). The results indicated that 24 h of waterlogging caused significant changes in mRNA abundance of 1,968 genes. Comprehensive gene ontology and functional enrichment analysis of root transcriptome revealed that waterlogging promoted responses to hypoxia and anaerobic respiration. On the other hand, the stress inhibited carbohydrate synthesis, cell wall biogenesis, and growth. The results also highlighted the roles of ethylene, nitrate, and nitric oxide in waterlogging acclimation. In addition, transcriptome profiling identified 85 waterlogging-induced transcription factors including members of AP2/ERF, MYB, and WRKY families implying that reprogramming of gene expression is a vital mechanism for waterlogging acclimation. Comparative analysis of differentially regulated transcripts in response to waterlogging among Arabidopsis, gray poplar, Jatropha, and rice further revealed not only conserved but species-specific regulation. Our findings unraveled the molecular responses to waterlogging in Jatropha and provided new perspectives for developing a waterlogging tolerant cultivar in the future.